Peningkatan Kemampuan Berpikir Kritis Peserta Didik Menggunakan Model Problem Based Learning Pada Pembelajaran IPAS - Putri Oktaviani; Sundahry; Abdulah (JURNAL KEILMUAN TEKNOLOGI DAN PENDIDIKAN TERPADU, 2026)
Abstract This research is motivated by the low critical thinking ability of students in science learning in grade I. The purpose of this study is to determine the improvement of the learning process and critical thinking ability of students using the Problem Based Learning (PBL) model. The method used is Classroom Action Research (CAR) which is carried out in two cycles. Each cycle consists of four stages, namely planning, implementation, observation, and reflection. The research subjects were 20 grade IV students. Data collection techniques were observation, tests, and documentation. In cycle I, the learning process of students reached 60% with a less good category. In cycle II, the learning process of students increased to 75% with a good category. In cycle I, the critical thinking ability of students reached 55% with a fairly critical category. In cycle II, the critical thinking ability increased to 75% with a critical category. Thus, it can be concluded that the Problem Based Learning model can improve the learning process and critical thinking ability of students in science learning in grade IV. This study shows that the Problem Based Learning model can be used as an alternative effective learning model to increase student involvement in the learning process and develop critical thinking skills in science learning in elementary schools. Keywords: Learning Process; Critical Thinking; Problem Based Learning; IPAS